Challenges and Opportunities of TLE Teachers in Philippine Public Schools: An Inquiry (British Journal of Multidisciplinary and Advanced Studies, 2023)
Gaining a comprehensive understanding of TLE teachers' professional landscape in Philippine public schools is essential for addressing the challenges and maximizing the opportunities they face. This study examines the challenges and opportunities encountered by TLE teachers in Philippine Public Schools, focusing on Region 10. Employing a thematic analysis approach following Saldana's framework, six TLE teachers from Junior and Senior High Schools were interviewed. The participants identified Human, Pedagogical, and Material issues as the primary problems they faced in their classes. Pedagogically, they struggled with implementing effective teaching approaches and sustaining students' interest. To address these concerns and enhance student learning, the teachers utilized their funds, extended their services, and sought support from stakeholders. They also recognized vocational training as an opportunity to improve their teaching. The study underscores the resilience and innovation exhibited by TLE teachers in overcoming these challenges. Their resourcefulness, commitment, and ability to leverage personal resources and engage stakeholders played a crucial role in mitigating the identified problems. Overall, this study emphasizes the importance of comprehensive support systems and policies to foster professional development and enhance the quality of TLE education in Philippine Public Schools.